2017
DOI: 10.1002/1873-3468.12537
|View full text |Cite
|
Sign up to set email alerts
|

Methylation‐independent adaptation in chemotaxis of Escherichia coli involves acetylation‐dependent speed adaptation

Abstract: Chemoreceptor methylation and demethylation has been shown to be at the core of the adaptation mechanism in Escherichia coli chemotaxis. Nevertheless, mutants lacking the methylation machinery can adapt to some extent. Here we carried out an extensive quantitative analysis of chemotactic and chemokinetic methylation-independent adaptation. We show that partial or complete adaptation of the direction of flagellar rotation and the swimming speed in the absence of the methylation machinery each occurs in a small … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…All the experiments were carried out at room temperature. The cell tracks were subsequently analyzed for angular velocities by homemade computer software .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the experiments were carried out at room temperature. The cell tracks were subsequently analyzed for angular velocities by homemade computer software .…”
Section: Methodsmentioning
confidence: 99%
“…However, methylation‐independent partial adaptation has also been reported . Recently, we demonstrated that methylation‐independent adaptation involves speed adaptation and that this adaptation is dependent on CheY acetylation . This raised the question of whether CheY acetylation is also involved in methylation‐dependent adaptation.…”
mentioning
confidence: 94%
“…Several studies in different bacterial species provided preliminary data that taxis systems and flagella can sense protein activities or changes in protein-protein interactions, reviewed in Anderson et al (2010), and also further outlined below. This may be of particular importance for motility functions, since they are required to provide a rapid response to changing environmental conditions, by modifications of either flagellar rotational speed or the direction of rotation (Baron et al, 2017;Koganitsky et al, 2019;Nieto et al, 2019), which are both important for the directionality of the biased random walk. Flagellar speed is set at the rotary motor and its interacting flagellar basal body proteins (Nesper et al, 2017).…”
Section: Modulation Of Motility and Taxis By Co-regulatory Protein-prmentioning
confidence: 99%
“…Furthermore, acetylation cross-talks with other PTMs on CheY. The CheY acetylation is closely related and co-regulated with phosphorylation ( Li et al, 2013), and maybe also associated with methylation-demethylation in chemokinetic adaptation (Baron et al, 2017). The acetylation of CheY is either through nonenzymatic acetylation using AcCoA as the acetyl donor, or through enzymatic acetylation by Acs using AcCoA or acetate.…”
Section: I34 Functional Consequences Of Bacterial Protein Acetylationmentioning
confidence: 99%